Lembaga Damai Dalam Proses Penyelesaian Perkara Perdata Di Pengadilan - Author: Mahyuni (Jurnal Hukum IUS QUIA IUSTUM, 2009)
The implementation of conciliation council in civil cases is urgently needed to give sense of justice among parties and to give limitation of cassation process. The limitation of cassation process is either substantively or procedurally. It is executed in order to reach reconciliation among parties which is stated on Article 130 HIR/154 R.Bg. Supreme Court had noticed to all judges by The Supreme Court Instruction No. 1/2002, that; The judges should act as a mediator in conciliation council and they gives a beneficial proposition for parties to entered negotiation in order to settle the dispute.Key word : civil case, conciliation council, and mediation